2020
DOI: 10.1007/s00228-020-02913-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of serotonin and norepinephrine transporters in antidepressant-induced arterial hypertension: a pharmacoepidemiological-pharmacodynamic study

Abstract: Purpose Some reports have described arterial hypertension (AH) in patients treated by serotonin reuptake inhibitor (SRI) or serotonin-norepinephrine reuptake inhibitor (SNRI) antidepressants. The mechanism remains discussed, some authors suggesting a role of SERT (SERotonin Transporter) inhibition whereas others discussing NET (NorEpinephrine Transporter) involvement. The present study used the pharmacoepidemiological-pharmacodynamic (PE-PD) method to investigate the role of these transporters in SRI-and SNRI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Niraparib was the only PARPi to have reported cases of hypertension (102.25 per 100 000 R x )—an established side effect to niraparib 56 —whereas the other PARPi had cases of hypotension. It has been hypothesised that hypertension might be produced due to an off‐target disruption of dopamine 57 and noradrenaline metabolism via the inhibition of DAT (dopamine transporter), NET (norepinephrine transporter) and SERT (serotonin transporter) by niraparib (Figure 1). 15 Despite the complexity associated with blocking several transporters and its potential opposing effects on blood pressure, it remains a plausible hypothesis 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Niraparib was the only PARPi to have reported cases of hypertension (102.25 per 100 000 R x )—an established side effect to niraparib 56 —whereas the other PARPi had cases of hypotension. It has been hypothesised that hypertension might be produced due to an off‐target disruption of dopamine 57 and noradrenaline metabolism via the inhibition of DAT (dopamine transporter), NET (norepinephrine transporter) and SERT (serotonin transporter) by niraparib (Figure 1). 15 Despite the complexity associated with blocking several transporters and its potential opposing effects on blood pressure, it remains a plausible hypothesis 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Niraparib was the only PARPi to have reported cases of hypertension (102.25 per 100 000 R x )-an established side effect to niraparib 56 whereas the other PARPi had cases of hypotension. It has been hypothesised that hypertension might be produced due to an off-target disruption of dopamine 57 and noradrenaline metabolism via the inhibition of DAT (dopamine transporter), NET (norepinephrine transporter)…”
Section: Vascular Adrs and Fatalitiesmentioning
confidence: 99%
“…However, Humbert et al analysed the WHO pharmacovigilance database and showed that the use of SSRIs significantly increases the risk of hypertension (30). Humbert et al suggested that hypertension can be a possible adverse effect explained by SERT inhibition and its vasoconstrictor effects and/or inhibited nitric oxidase vasodilatation effect, while the pharmacoepidemiologicalpharmacodynamic study found a positive correlation of the NET/SERT pKi ratio with the occurrence of hypertension in patients treated with SSRIs, as well as SNRIs (31). One cohort study in primary care in London was conducted to assess the risk of incident hypertension over 10 years and it showed the correlation of antidepressant use with developing hypertension (and other cardiovascular risks such as DM and hyperlipidaemia), possibly regarding the use of SSRIs in anxiety treatment (14).…”
Section: Effects Of Antidepressants On Blood Pressurementioning
confidence: 99%
“…That finding is important because nocturnal BP is reported to be a value predictor of cardiovascular mortality regardless of sex and age (34). Among SNRIs, venlafaxine shows a significantly higher risk of hypertension in a dose of 150 mg per day, but the risk is reduced by its extended release (ER) form (31). It is recommended that venlafaxine users be screened and monitored for hypertension, while duloxetine users are advised to monitor their BP if they have a prior diagnosis of hypertension or CVD (35).…”
Section: Effects Of Antidepressants On Blood Pressurementioning
confidence: 99%
“…Furthermore, there is a positive association between the binding affinities of SSRIs and SNRIs for norepinephrine and serotonin transporters and arterial HTN. 27 , 28 Based on this concept, we designed this retrospective study to assess both nighttime and daytime BP variability using 24‐hour ABPM in patients with and without psychiatric conditions and with or without SSRIs/SNRIs treatment. We hypothesized that patients on SSRIs/SNRIs would experience elevated BP, as measured by ABPM.…”
Section: Introductionmentioning
confidence: 99%